Multi-criteria decision framework for catalyst selection: Production of formic acid as a circular liquid organic hydrogen carrier in the hydrogen economy - Tekeli, Fatma Noyan; Filiz, Bilge Coskuner; Yoruklu, Hulya Civelek; Figen, Aysel Kanturk (ELSEVIER SCI LTD, 2024)
This study aims to use the multi-criteria decision analysis (MCDA) for the selection of suitable catalysts for the production of formic acid (FA), which serves as a circular liquid H2 carrier for the H2-carbon cycle. TOPSIS, VIKOR, ARAS, COPRAS, and PROMETHEE analytical decision-making methods were used to establish priority rankings for each method. With the exception of the top two ranks, the rankings differed across the methods. Therefore, we proposed an alternative ranking for the catalyst selection in the FA production, where all the methods' results were given equal priority. By aggregating the outcomes from the decision methods and sorting them in ascending order, a final prioritized ranking was established. Our results showed that the proposed MCDA method was effective in identifying the most suitable catalyst for the FA production as a circular LOHC in the H2carbon cycle. The model determined that Pd nanoparticle-based activated carbon-supported catalyst exhibited high activity, selectivity, and stability, while also being cost-effective. The findings of this study might contribute to the development of more efficient H2 storage systems based on FA.
Keywords: Circular hydrogen; Formic acid; LOCHs; Catalysts; Multi -criteria decision method; CARBON-DIOXIDE HYDROGENATION; CO2 HYDROGENATION; AQUEOUS-SOLUTION; STORAGE; SYSTEM; NANOPARTICLES; FORMATE; FUTURE; NANOCATALYST; BICARBONATE; Science & Technology - Other Topics; Engineering; Environmental Sciences & Ecology